First synthesis of 2-(benzofuran-2-yl)-6,7-methylene dioxyquinoline-3-carboxylic acid derivatives - Gao, Wentao; Liu, Jia; Jiang, Yun; Li, Yang (Beilstein Journal of Organic Chemistry, 2011)
A facile and inexpensive synthesis of a series of novel methylenedioxy-bearing 2-(benzofuran-2-yl)-quinoline-3-carboxylic acid derivatives 3a–h via the one-pot reaction of ethyl 2-chloromethyl-6,7-methylenedioxyquinoline-3-carboxylate (5) with various substituted salicylaldehydes 6a–g as well as 2-hydroxy-1-naphthaldehyde (6h) is described. Substrate 5 was synthesized by the Friedländer condensation reaction of 2-amino-4,5-methylenedioxybenzaldehyde (4) with ethyl 4-chloro-3-oxobutanoate using KHSO4 as catalyst under ultrasound irradiation conditions. The targeted compounds 3a–h were obtained in good yields of 52–82% and their structures were established based on spectral data and elemental analyses.
Keywords: benzofuran; Friedländer condensation; methylenedioxy-bearing; one-pot; quinoline-3-carboxylic acid; salicylaldehyde

(untitled) - Cimanga, K.; De Bruyne, T.; Pieters, L.; Vlietinck, A. J. (J. Nat. Prod., 1997)

(untitled) - Jonckers, T. H. M.; van Miert, S.; Cimanga, K.; Bailly, C.; Colson, P.; De Pauw-Gillet, M.-C.; van den Heuvel, H.; Claeys, M.; Lemière, F.; Esmans, E. L.; Rozenski, J.; Quirijnen, L.; et al. (J. Med. Chem., 2002)

(untitled) - Witherup, K. M.; Ransom, R. W.; Graham, A. C.; Bernard, A. M.; Salvatore, M. J.; Lumma, W. C.; Anderson, P. S.; Pitzenberger, S. M.; Varga, S. L. (J. Am. Chem. Soc., 1995)

(untitled) - Balamurugan, K.; Jeyachandran, V.; Perumal, S.; Manjashetty, T. H.; Yogeeswari, P.; Sriram, D. (Eur. J. Med. Chem., 2010)

(untitled) - Chen, Y.-L.; Zhao, Y.-L.; Lu, C.-M.; Tzeng, C.-C.; Wang, J.-P. (Bioorg. Med. Chem., 2006)

(untitled) - Meléndez Gómez, C. M.; Kouznetsov, V. V.; Sortino, M. A.; Álvarez, S. L.; Zacchino, S. A. (Bioorg. Med. Chem., 2008)

(untitled) - Yadav, J. S.; Reddy, B. V. S.; Vishnumurthy, P.; Premalatha, K. (Synthesis, 2008)

(untitled) - Verniest, G.; Wang, X.; De Kimpe, N.; Padwa, A. (J. Org. Chem., 2010)

(untitled) - Fuganti, C.; Serra, S. (Tetrahedron Lett., 1998)

(untitled) - Abdel-Wahab, B. F.; Abdel-Aziz, H. A.; Ahmed, E. M. (Eur. J. Med. Chem., 2009)

(untitled) - Akgul, Y. Y.; Anil, H. (Phytochemistry, 2003)

(untitled) - Aslam, S. N.; Stevenson, P. C.; Phythian, S. J.; Veitch, N. C.; Hall, D. R. (Tetrahedron, 2006)

(untitled) - Stevenson, P. C.; Veitch, N. C. (Phytochemistry, 1998)

(untitled) - Lages, A. S.; Silva, K. C. M.; Miranda, A. L. P.; Fraga, C. A. M.; Barreiro, E. J. (Bioorg. Med. Chem. Lett., 1998)

(untitled) - Chan, G. W.; Mong, S.; Hemling, M. E.; Freyer, A. J.; Offen, P. M.; DeBrosse, C. W.; Sarau, H. M.; Westley, J. W. (J. Nat. Prod., 1993)

(untitled) - Kupchan, S. M.; Britton, R. W.; Ziegler, M. F.; Gilmore, C. J.; Restivo, R. J.; Bryan, R. F. (J. Am. Chem. Soc., 1973)

(untitled) - Micale, N.; Zappalà, M.; Grasso, S. (Farmaco, 2002)

(untitled) - Leite, A. C. L.; da Silva, K. P.; de Souza, I. A.; de Araújo, J. M.; Brondani, D. J. (Eur. J. Med. Chem., 2004)

(untitled) - Bezerra-Netto, H. J. C.; Lacerda, D. I.; Miranda, A. L. P.; Alves, H. M.; Barreiro, E. J.; Fraga, C. A. M. (Bioorg. Med. Chem., 2006)

(untitled) - Öztürk, S. E.; Akgül, Y.; Anil, H. (Bioorg. Med. Chem., 2008)

(untitled) - Chen, G. L.; Yang, L.; Rowe, T. C.; Halligan, B. D.; Tewey, K. M.; Liu, L. F. (J. Biol. Chem., 1984)

(untitled) - Capilla, A. S.; Sánchez, I.; Caignard, D. H.; Renard, P.; Pujol, M. D. (Eur. J. Med. Chem., 2001)

(untitled) - Castro, A.; del Corral, J. M. M.; Gordaliza, M.; Grande, C.; Gómez-Zurita, A.; García-Grávalos, D.; San Feliciano, A. (Eur. J. Med. Chem., 2003)

(untitled) - Imperio, D.; Pirali, T.; Galli, U.; Pagliai, F.; Cafici, L.; Canonico, P. L.; Sorba, G.; Genazzani, A. A.; Tron, G. C. (Bioorg. Med. Chem., 2007)

(untitled) - Chou, L.-C.; Chen, C.-T.; Lee, J.-C.; Way, T.-D.; Huang, C.-H.; Huang, S.-M.; Teng, C.-M.; Yamori, T.; Wu, T.-S.; Sun, C.-M.; Chien, D.-S.; Qian, K.; et al. (J. Med. Chem., 2010)

(untitled) - Dolle, R. E.; Nelson, K. H., Jr (J. Comb. Chem., 1999)

(untitled) - Li, Y.; Zhang, C.-H.; Sun, M.-C.; Gao, W. T. (J. Heterocycl. Chem., 2009)

(untitled) - Gao, W. T.; Zhang, X.-F.; Li, Y.; Liu, H.-Y.; Imafuku, K. (Heterocycles, 2010)

(untitled) - Gao, W. T.; Cheng, X. P.; Li, Y. (Heterocycles, 2010)

(untitled) - Li, Y.; Gao, W. T. (Beilstein J. Org. Chem., 2010)

(untitled) - Yue, D.; Yao, T.; Larock, R. C. (J. Org. Chem., 2005)

(untitled) - Larock, R. C.; Yum, E. K.; Doty, M. J.; Sham, K. K. C. (J. Org. Chem., 1995)

(untitled) - Yue, D.; Larock, R. C. (J. Org. Chem., 2002)

(untitled) - Larock, R. C.; Harrison, L. W. (J. Am. Chem. Soc., 1984)

(untitled) - Jacubert, M.; Hamze, A.; Provot, O.; Peyrat, J.-F.; Brion, J.-D.; Alami, M. (Tetrahedron Lett., 2009)

(untitled) - Chittimalla, S. K.; Chang, T.-C.; Liu, T.-C.; Hsieh, H.-P.; Liao, C.-C. (Tetrahedron, 2008)

(untitled) - Ledoussal, B.; Gorgues, A.; Le Coq, A. (Tetrahedron, 1987)

(untitled) - Dupont, R.; Cotelle, P. (Synthesis, 1999)

(untitled) - Dupont, R.; Cotelle, P. (Tetrahedron, 2001)

(untitled) - Dupont, R.; Cotelle, P. (Tetrahedron Lett., 2001)

(untitled) - Srivastava, V.; Negi, A. S.; Kumar, J. K.; Faridi, U.; Sisodia, B. S.; Darokar, M. P.; Luqman, S.; Khanuja, S. P. S. (Bioorg. Med. Chem. Lett., 2006)